2016
DOI: 10.1515/msp-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of 0.7(Fe2O3)/0.3(ZnO) nanocomposites in nanopowder form and dispersed in polymer matrix

Abstract: Magnetic properties of 0.7(Fe 2 O 3 )/0.3(ZnO) nanocomposite synthesized by traditional wet chemistry method and containing only two phases: ZnO (nonmagnetic) and ZnFe 2 O 4 (magnetic, with nanocrystallites of average size 12 nm, but forming large agglomerates, up to 100 nm in size) were studied by DC magnetization and ferromagnetic resonance (FMR). The investigated nanocomposite was either in a form of nanopowder or dispersed at concentration of 0.1 wt.% in poly(ethylene naphthalate-block-tetramethylene oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…Typek et al [24] measured the M s and H c values for the nanopowder sample, and the results of their study indicated that the M s value was smaller than the present study results; however, the H c values were higher. As compared to other studies, the observation of such decreased H c values for composite in the present study can be attributed to the formation of composite structure with high Table 2: The values of surface area and pore volume for poly(4,4′-cyclohexylidene bisphenol oxalate).…”
Section: Magnetic Properties Of Poly(44′-cyclohexylidene Bisphenolcontrasting
confidence: 72%
“…Typek et al [24] measured the M s and H c values for the nanopowder sample, and the results of their study indicated that the M s value was smaller than the present study results; however, the H c values were higher. As compared to other studies, the observation of such decreased H c values for composite in the present study can be attributed to the formation of composite structure with high Table 2: The values of surface area and pore volume for poly(4,4′-cyclohexylidene bisphenol oxalate).…”
Section: Magnetic Properties Of Poly(44′-cyclohexylidene Bisphenolcontrasting
confidence: 72%